Policy innovation in public services: the project development of public service mall in Barru Regency, Indonesia - Ali, Kasmiah; Idris, Ahmad Syahir; Haruna, Masyita (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
Public service innovation has become a strategic approach to improving the quality of public services in many places in Indonesia. This study analyzes the development of the Public Service Mall (PSM) in Barru Regency as an integrated service model that aims to improve efficiency, accessibility, and community satisfaction. Using a qualitative explanatory case study approach, data was collected through in-depth interviews, direct observation, and analysis of official documents. The results showed that PSM in Barru Regency has increased the speed and convenience of public services by decreasing bureaucratic complexity and consolidating various service units into one single location. However, several challenges remain, particularly in terms of inter-agency coordination, human resource capacity, and digital infrastructure development. This research provides a critical analysis of such barriers and suggests policy recommendations to strengthen governance mechanisms, standardize services, and encourage public participation. Finally, this research contributes to the academic discourse on public service innovation and offers practical insights for replicating and refining integrated publis service delivery models in other regions of Indonesia.